SABUWA PITATE DALAM PANTEKOSTALISME MEMBENTUK IDENTITAS KOMUNITAS PANTEKOSTA DI KABUPATEN MINAHASA TENGGARA. - Ridwan Arke Rokot; Benny B. Binilang; Heldy Rogahang (Manna Rafflesia, 2025)
This study describes, analyses, reflects and interprets the concept and praxis of Pentecostalism religiosity inspired by the philosophy of sabuwa pitate in traditional cultural architecture in the pioneer community of Pentecostal GPdI in Southeast Minahasa. Using a narrative qualitative method, data were collected through participatory observation, in-depth interviews, and documentation. The findings show the integration of Pentecostal teaching values with Minahasa local wisdom, the experience of the Holy Spirit, and worship practices that emphasise togetherness and kinship. This research will make an important contribution in understanding and developing the concept and praxis of Pentecostalism religiosity, the constructive approach between religious and cultural values, and the elaboration of the application of these values in Christian education and community life. Therefore, the conclusion and novelty of this research emphasise that the integration of Pentecostalism and Sabuwa Pitate values has great potential to encourage inclusive and sustainable social transformation. GPdI, the government, and the community need to work together to realise this. GPdI can be a catalyst for change through relevant programmes, the government can integrate religious values in public policy, and the community can play an active role as agents of change. This research opens up opportunities for the development of science and public policies that are more in favour of the community.